Factors Influencing and Problems Faced by Farmers in the Adoption of Biostimulants in Dantiwada Taluka of Banaskantha District, Gujarat - , Darshit B. Barvadiya; , Dilip R. Vahoniya; , Himan R. Patel (Archives of Current Research International, 2025)
Agriculture is the backbone of the Indian economy. Approximately 60 to 70 percent of the Indian population is engaged in agriculture, contributing nearly 20 percent to the nation’s GDP. Recently, there has been a notable shift in agricultural input practices, with various agencies emphasizing the use of biological alternatives such as biostimulants. This study investigates the factors influencing and the challenges faced by farmers in adopting biostimulants in Dantiwada Taluka of Banaskantha District, Gujarat. Using multi-stage sampling, 200 farmers were selected as respondents. The results revealed that a majority of the farmers (78%) belonged to the 36-50 years age group, and nearly 79 per cent had a family size of 3 to 5 members. In terms of education, 27 per cent of the respondents had primary education, 50.5 per cent had completed secondary education (SSC), and 21 per cent had higher secondary education (HSC). Most farmers engaged in farming along with animal husbandry, with a majority earning between ₹1 lakh and ₹5 lakhs annually. The average landholding was between 2 to 5 acres. Regarding crop patterns, groundnut was the dominant crop during the Kharif season (100%), potato was the most cultivated crop in Rabi, followed by wheat, mustard, and amaranth. In the Zayad season, groundnut again led, followed by pearl millet, muskmelon, and watermelon. Survey findings indicated that 82.5 per cent of the farmers were aware of biostimulants, and among them, 86 per cent had used them in their fields. Most users believed that biostimulants enhanced flowering and increased crop yields. Dealer and distributor recommendations were the most influential factor in encouraging farmers to adopt biostimulants. The primary challenges identified were the lack of proper technical knowledge and the delayed visible effects of biostimulants. Despite these challenges, the market potential analysis showed promising opportunities. The projected seasonal market for biostimulants in Dantiwada was valued at approximately ₹5.25 crore, indicating considerable demand.